2021
DOI: 10.1007/s00044-021-02701-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo biological activities of azulene derivatives with potential applications in medicine

Abstract: Azulene is an aromatic hydrocarbon that possesses a unique chemical structure and interesting biological properties. Azulene derivatives, including guaiazulene or chamazulene, occur in nature as components of many plants and mushrooms, such as Matricaria chamomilla, Artemisia absinthium, Achillea millefolium, and Lactarius indigo. Due to physicochemical properties, azulene and its derivatives have found many potential applications in technology, especially in optoelectronic devices. In medicine, the ingredient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 63 publications
1
29
0
1
Order By: Relevance
“…Their tumor-specificity was matched at a higher probability with the onset of a signaling pathway of NFκB, and receptors for estrogen, thyroid stimulating hormone, and glucocorticoid ( Figure 7 ). This is consistent with the reported anti-inflammatory activity of guaiazulene [ 4 , 9 , 20 , 21 , 22 ]. On the other hand, the involvement of other signaling pathways such as caspase and androgen receptor ( Figure S7 ), transforming growth factor β (TGFβ), peroxisome proliferator activated receptor δ (PPARδ), endoplasmic reticulum stress (ER stress) response, and retinoid X receptor-α(RXR) ( Figure S8 ) seems to be low.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Their tumor-specificity was matched at a higher probability with the onset of a signaling pathway of NFκB, and receptors for estrogen, thyroid stimulating hormone, and glucocorticoid ( Figure 7 ). This is consistent with the reported anti-inflammatory activity of guaiazulene [ 4 , 9 , 20 , 21 , 22 ]. On the other hand, the involvement of other signaling pathways such as caspase and androgen receptor ( Figure S7 ), transforming growth factor β (TGFβ), peroxisome proliferator activated receptor δ (PPARδ), endoplasmic reticulum stress (ER stress) response, and retinoid X receptor-α(RXR) ( Figure S8 ) seems to be low.…”
Section: Discussionsupporting
confidence: 92%
“…Azulene derivatives, including guaiazulene ( Figure S1A ), are present in many plants and mushrooms, and applied as optoelectronic devices and ingredients used for hundreds of years in antiallergic, antibacterial, and anti-inflammatory therapies [ 4 ]. Several research studies have reported the applications of azulenes on oral diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The introspection of the spectrum of the volatile organic mixture from different Muscodor species has revealed the antibacterial spectrum of some commonly occurring entities such as isobutyric acid [209][210][211], β-bisabolol and azulene and its derivatives [212]. Thus, creating artificial mixtures and evaluating them for their anti-bacterial activities may prove to be very useful for preventing drug-resistant film-forming bacteria from causing infections in clinical as well as non-clinical settings.…”
Section: Volatile Organic Compounds (Vocs)mentioning
confidence: 99%
“…It has been suggested that the hydrophobic structure and the dihedral angle of the two benzene rings are important for the development of ERα antagonists or ERα partial agonists. Guaiazulene and its derivatives (Figure 2) are widely used in pharmaceuticals and cosmetics because of their moderate anti-inflammatory activities [16]. Azulene, the central skeleton of guaiazulene, is a typical non-benzene aromatic compound that has a fused-ring structure composed of cyclopentadiene and cycloheptatriene [17].…”
Section: Introductionmentioning
confidence: 99%